2018
DOI: 10.1002/ijc.31275
|View full text |Cite
|
Sign up to set email alerts
|

EML4‐ALK fusion variant V3 is a high‐risk feature conferring accelerated metastatic spread, early treatment failure and worse overall survival in ALK+ non‐small cell lung cancer

Abstract: In order to identify anaplastic lymphoma kinase-driven non-small cell lung cancer (ALK NSCLC) patients with a worse outcome, who might require alternative therapeutic approaches, we retrospectively analyzed all stage IV cases treated at our institutions with one of the main echinoderm microtubule-associated protein-like 4 (EML4)-ALK fusion variants V1, V2 and V3 as detected by next-generation sequencing or reverse transcription-polymerase chain reaction (n = 67). Progression under tyrosine kinase inhibitor (TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 33 publications
6
103
1
1
Order By: Relevance
“…in the number of metastatic sites at diagnosis and OS, according to the type of TP53 mutation and involved TP53 exon. In contrast, similar to the smaller cohort in a previous study (including 52 newly diagnosed stage IV patients instead of 81 in our study), V3‐positive cases had more metastatic sites at diagnosis than V1 and V2 patients (mean 3.2 vs. 1.8 and 1.7 respectively, Table and Supporting Information Fig. 3), which appeared similar and were therefore grouped together for further analyses.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…in the number of metastatic sites at diagnosis and OS, according to the type of TP53 mutation and involved TP53 exon. In contrast, similar to the smaller cohort in a previous study (including 52 newly diagnosed stage IV patients instead of 81 in our study), V3‐positive cases had more metastatic sites at diagnosis than V1 and V2 patients (mean 3.2 vs. 1.8 and 1.7 respectively, Table and Supporting Information Fig. 3), which appeared similar and were therefore grouped together for further analyses.…”
Section: Resultssupporting
confidence: 84%
“…4 from the diagnosis of metastatic disease. 5 comparisons of V3 vs. V1/V2 and TP53mut vs. TP53wt patients were performed with an unpaired t-test for numerical and with a chi-square test for categorical data; significant results (p < 0.05) are noted with asterisks. statistical comparison by Cox regression; in cases when more than one factors showed significant effects, these were additionally analyzed together, using the DN subgroup as reference.…”
Section: Diagnosis Of Lung Adenocarcinoma and Detection Of Eml4-alk Fmentioning
confidence: 99%
“…According to these publications, variant V3 tends to be a higher risk feature associated with poor prognosis compared with variant V1. [25][26][27] The present study identified that , several studies reported that the ALK G1202R mutation is associated with first-generation and second-generation ALK-TKI resistance, and third-generation ALK-TKI, including lorlatinib, potentially overcome this resistance. 60,61 The unsatisfactory clinical response of brigatinib treatment in the current case also suggests that there should be more focus on individualized medicine in cancer treatment, rather than a total dependence on relevant guidelines for the guidance of treatment decisions.…”
Section: Discussionmentioning
confidence: 52%
“…An increasing number of studies have reported that patients with different EML4-ALK variants show heterogeneous clinical outcomes to ALK-TKI for NSCLC. [25][26][27] Therefore, we hypothesized that molecular or clinical characteristics associated with different variants might show some difference. In the present study, the age of patients with variant V1 was significantly younger compared with that of patients with variant V3.…”
Section: Genomic Heterogeneity Of Alk Rearrangementsmentioning
confidence: 99%
“…Although FISH remains gold standard for fusion detection, other RNA-based assays such as the targeted NGS used here or Nanostring show higher predictive value for response to treatment. 35 Along the same lines, other recent studies have reported an increased frequency of ALK resistance mutations in V3-positive NSCLC, 36 as well as a worse PFS for V3-driven TKI-treated tumors. This is becoming increasingly important, because accumulating data suggest that several fusion variants have prognostic and predictive significance.…”
Section: Discussionmentioning
confidence: 86%